Mosses (Bryophyta) of the north-western region of Marambio (Seymour) Island, Antarctica - Cottet, Agustina Celeste (2025)
Marambio (Seymour) Island is located in the James Ross Archipelago east of the Antarctic Peninsula. Although several research groups have carried out studies on the biodiversity on the island for decades, surveys of bryophytes have not been developed. That is why there are currently only six species of mosses recorded in the northern part of the island. During the 2021–2022 summer Antarctic field trip, 15 mosses species were surveyed in Marambio Island. Of the total number of collected species, nine are reported for the first time for Marambio Island. For the remaining four species, their distributions are now expanded to Marambio Island.